Penggunaan Metode ARIMA dalam Peramalan Nilai Ekspor Non-Migas Indonesia Tahun 2023 - Dwi Agustin Retnowardani; Wahyu Nur Achmadin (MathVisioN, 2023)
International trade can help a country increase its production capacity and increase its economic development at home, seeing advantages from abroad and vice versa. The value of Indonesia's non-oil and gas exports from January 2022 to July 2023 is the data needed to be analyzed in this research. This study uses the Box-Jenkins periodic series (ARIMA) method. In this research, the following methods were used: (1) Collecting secondary data from the Central Statistics Agency of the Republic of Indonesia; (2) Identify the ARIMA model; (3) Checking stationary data; (4) Determine the ARIMA model for forecasting; (5) Using models for forecasting; and (7) drawing conclusions. This research produces forecasting results for the value of Indonesia's non-oil and gas exports over five periods. Namely, in August 2023, the value may reach 1.67945 million USD, in September 2023, the value may reach 1.73242 million USD, in October 2023, the value may reach 1.75278 million USD, in November 2023, the value it may reach 1.76061 million USD, and in September 2023, its value may reach 1.76362 million USD.